Investment driving forces afecting Lithuanian economic growth - Tvaronaviciene, Manuela (Journal of Business Economics and Management, 2006)
Presented publication presents a complex research model embracing a series of investigations related to assessment of driving forces affecting economic growth processes in Lithuania. New approach towards impact of foreign direct investment (FDI) on economic development of transition country is emphasized. Speculations on FDI efficiency follow elaboration of factors initiating FDI. FDI and foreign trade are seen as specific factors affecting restructuring of transition country as it follows consistent patterns of development. Policy implications are formulated.First published online: 14 Oct 2010